2021
DOI: 10.1521/soco.2021.39.3.366
|View full text |Cite
|
Sign up to set email alerts
|

(Eye-) Tracking the Other-Race Effect: Comparison of Eye Movements During Encoding and Recognition of Ingroup Faces With Proximal and Distant Outgroup Faces

Abstract: People experience difficulties recognizing faces of ethnic outgroups, known as the other-race effect. The present eye-tracking study investigates if this effect is related to differences in visual attention to ingroup and outgroup faces. We measured gaze fixations to specific facial features and overall eye-movement activity level during an old/new recognition task comparing ingroup faces with proximal and distal ethnic outgroup faces. Recognition was best for ingroup faces and decreased gradually for proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Alternatively, because outgroup targets are less likely to be relevant enough to motivate individuation (Fiske & Neuberg, 1990), they propose that people will focus on shared categorical features when processing outgroups. In accordance with this theorizing, Kawakami and colleagues (Friesen, Kawakami, Vingilis‐Jaremko, et al, 2019; Kawakami et al, 2014) found that White perceivers attend more to the eyes of White ingroup compared to Black outgroup targets (see also Arizpe et al, 2016; Burgund, 2021; Stelter et al, 2021; Wheeler et al, 2011; but see Hills & Pake, 2013; McDonnell et al, 2014). This preference for ingroup eyes has also been found for White ingroup and Asian outgroup targets (Arizpe et al, 2016; Brielmann et al, 2014; Wu et al, 2012; but see Burgund, 2021; Caldara et al, 2010).…”
Section: Mechanisms For Differences In Processing Ingroup and Outgrou...mentioning
confidence: 73%
See 3 more Smart Citations
“…Alternatively, because outgroup targets are less likely to be relevant enough to motivate individuation (Fiske & Neuberg, 1990), they propose that people will focus on shared categorical features when processing outgroups. In accordance with this theorizing, Kawakami and colleagues (Friesen, Kawakami, Vingilis‐Jaremko, et al, 2019; Kawakami et al, 2014) found that White perceivers attend more to the eyes of White ingroup compared to Black outgroup targets (see also Arizpe et al, 2016; Burgund, 2021; Stelter et al, 2021; Wheeler et al, 2011; but see Hills & Pake, 2013; McDonnell et al, 2014). This preference for ingroup eyes has also been found for White ingroup and Asian outgroup targets (Arizpe et al, 2016; Brielmann et al, 2014; Wu et al, 2012; but see Burgund, 2021; Caldara et al, 2010).…”
Section: Mechanisms For Differences In Processing Ingroup and Outgrou...mentioning
confidence: 73%
“…While our brief review provides some evidence for both experience and motivation as explanations for differences in processing ingroup and outgroup faces, such as the ORE and biases in emotion identification, it is clear that this support is neither strong nor consistent (Stelter et al, 2021). Given that these mechanisms may work alone or in conjunction to predict certain face processes, recent theories have attempted to integrate these mechanisms into a single framework Tüttenberg & Wiese, 2019).…”
Section: Motivation and Emotion Identificationmentioning
confidence: 93%
See 2 more Smart Citations
“…Likewise, Black participants showed better recognition for White than East Asian faces. Stelter et al (2021) further found that majority participants differentiated between outgroups that constituted relatively large and small minority populations in their environment. Specifically, White participants in Germany showed better recognition of Middle Eastern targets (a relatively large minority group) compared to Black or Asian targets (relatively small minority groups).…”
Section: Introductionmentioning
confidence: 98%